Accesibilitatea studenților cu deficiențe de vedere în universitățile clujene - Guttman, Filip (Calitatea Vieții, 2011)
This paper is the result of a research that investigates how the accessibility of higher education is perceived by people with visual impairments, without disabilities. The first chapter introduces the reader to the main topic of this research. The next chapter includes the research approach and results. The research investigates two groups of students with visual impairments, without disabilities from “BabesBolyai” University, Cluj-Napoca. The research-tools are two questionaires with open questions. In analyzing the collected data is used the software for qualitative data Atlasti, and the results are presented through a comparative approach. Generally, there aren’t major difficulties identified in the accessibility of higher education, and positive attitudes mark the behavior towards people with visual impairments. With few exceptions, students with visual impairments do not face big problems and attitudinal barriers in their acces to university. The nature of this phenomenological research has it epistemological limits, requiring a more in-depth and extended analysis.